Improvement in yield and fibre quality using interspecific hybridization in cotton (Gossypium spp) - XIAOQUAN, ZHANG; XUEDE, WANG; DUTT, YAGYA (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2002–04 to improve fibre quality and seed cotton yield simultaneously in cotton (Gossypium spp). For this purpose 2 types of hybrids, i e interspecific (G. hirsutum × G. barbadense) and intraspecific (G. hirsutum × G. hirsutum) were developed during 2002–03 and were evaluated for yield and fibre quality traits during 2003–04. The range of heterosis was ranged from –32.18 (‘HaiA’ × ‘LuR’) to 20.59% (‘HaiB’ × ‘JiR’) for seed cotton yield, –42.22 (‘HaiA’ × ‘LuR’) to 8.60% (‘JiA’ × ‘LuR’) for lint yield, –23.80 (‘HaiB’ × ‘JiR’) to 0.75% (‘JiA’× ‘LuR’) for lint per cent, –31.50 (‘LuA’× ‘HiR’) to 3.87% (‘JiA’× ‘LuR’) for boll weight and – 15.71 (‘JiA’ × ‘JiR’) to 106.43% (‘HaiB’ × ‘JiR’) for bolls/plant, –3.90 (‘JiA’ × ‘JiR’) to 27.29% (‘HaiR’ × ‘LuR’) for fibre length, –6.37 (‘JiA’ × ‘JiR’) to 35.93% (‘LuA’ × ‘HR2’) for fibre strenght, –2.19 (‘JiA’ × ‘JiR’) to 4.38% (‘JiA’ × ‘HR1’) for fibre elongation and –0.42 (‘HaiA’ × ‘LuR’) to 3.53% (‘JiR’ × ‘HaiR’) for fibre uniformity. All interspecific hybrids were observed superior in fibre quality as compared to check. Among these hybrid ‘HaiB × ‘JiR’ showed significantly positive heterosis for seed cotton yield over the commercial check ‘LMY 15’. This hybrid having significantly higher yield then check and also good for fibre quality traits could be exploited at commercial level after multilocartional testing. Other hybrids observing good fibre quality traits could be used as a breeding material for improvement in fibre quality.